Improving Children's Language and Literacy Through Snakes and Ladders Game: Peningkatan Literasi Bahasa dan Sastra Anak Melalui Media Pembelajaran Permainan Ular Tangga - Pratikno, Heru; Rosenda, Diden; Baskin, Askurifai (Transformatika: Jurnal Bahasa, Sastra, dan Pengajarannya, 2025)
The rapid flow of globalization and modernization that has hit the Indonesian nation has made character education increasingly eroded. This can be proven by seeing the decreasing character of students regarding their use of language and impolite speech. Apart from that, students' interest in reading a text is decreasing, they may not even understand what they are reading. They are more interested in their respective cellphones which are only used for playing games, watching films, and even using social media. On the other hand, teachers' lack of language skills is a factor in slowing the transfer of knowledge to students. Therefore, the role of school teachers is needed to straighten students' characters and increase their interest in reading. The way to do this is through fun language and literature learning. So, the aim of this research is that the author wants to know how to improve student character and literacy through creative digital-based literary learning media. The method used in this service is class action through teachers. The result of achieving the target of this service is an increase in the teacher's ability to strengthen student character and student interest in reading.